Regional analgesia for lower leg trauma and the risk of acute compartment syndrome: Guideline from the Association of Anaesthetists. (6th June 2021) - Nathanson, M. H.; Harrop‐Griffiths, W.; Aldington, D. J.; Forward, D.; Mannion, S.; Kinnear‐Mellor, R. G. M.; Miller, K. L.; Ratnayake, B.; Wiles, M. D.; Wolmarans, M. R.
Summary: Pain resulting from lower leg injuries and consequent surgery can be severe. There is a range of opinion on the use of regional analgesia and its capacity to obscure the symptoms and signs of acute compartment syndrome. We offer a multi‐professional, consensus opinion based on an objective review of case reports and case series. The available literature suggested that the use of neuraxial or peripheral regional techniques that result in dense blocks of long duration that significantly exceed the duration of surgery should be avoided. The literature review also suggested that single‐shot or continuous peripheral nerve blocks using lower concentrations of local anaesthetic drugs without adjuncts are not associated with delays in diagnosis provided post‐injury and postoperative surveillance is appropriate and effective. Post‐injury and postoperative ward observations and surveillance should be able to identify the signs and symptoms of acute compartment syndrome. These observations should be made at set frequencies by healthcare staff trained in the pathology and recognition of acute compartment syndrome. The use of objective scoring charts is recommended by the Working Party. Where possible, patients at risk of acute compartment syndrome should be given a full explanation of the choice of analgesic techniques and should provide verbal consent to their chosen technique, which should be documented. Although the patient has the right to refuse any form of treatment, such as the analgesic technique offered or the surgical procedure proposed, neither the surgeon nor the anaesthetist has the right to veto a treatment recommended by the other.